A INTACT REVIEW ON NELUMBO NUCIFERA W.S.R TO ITS THERAPEUTIC POTENTIAL - Chhavi, *Yadav; Suresh, Chaubey; Tejbeer, Singh; D.C, Singh; Sangeeta, Kumari (International Journal of Ayurveda and Pharma Research, 2016)
Last few decades have again shown a notable interest in herbal products for food or in medicinal aspect, the reason behind this is the increasing awareness about the limitations of the synthetic agents. Kamal is a well known plant in ancient medical sciences. It is extensively described in almost all Samhitas and Nighantus of Ayurveda, which reflects its great medicinal value. It has been used extensively by Ayurvedic Physicians for centuries to treat a wide variety of disorders. It is edible used for food and medicine both. Kamal is Nelumbo nucifera Grertn (syn. Nelumbium speciosum Willd.; Nymphaea nelumbo Linn.) of Nelumbonaceae family. It is a perennial aquatic herb bearing the famous red lotus flowers. It has miraculous cooling effect and anti-haemorrhagic property. Its flowers contain robinin an glucoside. Leaves contains nuciferine an alkaloid, asmilobine & irinidine. Root contain isoliensinine neferine, seed contains armeparine. The different part contains different chemical constituents which enhance its medicinal value in different diseases. This article review the Ayurvedic literature, traditional uses, phytochemistry & therapeutic reports on different parts of N. nucifera. The review also describes various compound isolated from different parts of this plant & the therapeutic benefits derived from those phytoconstituents.